Corporate real estate management: a survey of the South African entertainment & media companies - Selamolela, Matla (My University, 2017)
Purpose- The main objective of this study was to determine a particular knowledge and skill of the senior management of the South African entertainment and media industry towards corporate real estate management. [Abbreviated Abstract. Open document to view full version]
Thesis is submitted in partial fulfilment for the degree of Master of Science in property development and Management to the Faculty of Engineering and the Built Environment, School of Construction Economics and Management at the University of the Witwatersrand, Johannesburg, 2017
Keywords: Corporate real estate management; Entertainment and media; Knowledge and attitudes; Lease accounting; Real estate management--South Africa; Real property--South Africa; Architecture and Media; Commercial real estate--South Africa--Management